Sustained viral remission with directly acting antivirals in the treatment of chronic hepatitis C among adolescent (12-17 years) survivors of childhood leukemia - Nadar Sobhan, Prasanth Kunjan; Sarojam, Bindu (International Journal of Contemporary Pediatrics, 2021)
Studies from India highlight the high prevalence of hepatitis C (6-25%) infection in survivors of childhood cancers. Recently Directly acting antivirals (DAA) have been approved for treatment of Chronic hepatitis C (CHC) in children >12 years of age. Even though there are reports of efficacy and safety of DAAs in the treatment of CHC in hematologic disorders like thalassemia, there is minimal data on the efficacy of DAA in the management of chronic hepatitis C among adolescent survivors of childhood leukaemia. We performed this retrospective analysis to study Sustained viral remission (SVR) with DAA in the treatment of CHC among adolescent (12-17 years) survivors of childhood leukemia. This study also aimed to analyze the genotypic profile of hepatitis C virus and adverse effects of the DAA in this group of adolescents (12-17 years). 5 adolescents (12-17 years) who were diagnosed with CHC during August 2017 to May 2020 were enrolled in this observational study. All belonged to genotype 1; received DAA regimen comprising of sofosbuvir 400 mg and ledipasvir 90 mg for 12 weeks with good drug compliance and no major adverse effects. All of them attained SVR at 12 weeks after completing treatment. This study among adolescent survivors of childhood leukaemia with chronic hepatitis C genotype 1, augments data regarding efficacy of a 12 weeks DAA regimen comprising of sofosbuvir 400 mg and ledipasvir 90 mg in the attainment of SVR at 12 weeks after completing treatment.